Association between suicide method, and gender, age, and education level in Iran over 2006–2010. (22nd August 2013) - Shojaei, Ahmad; Moradi, Saadolah; Alaeddini, Farshid; Khodadoost, Mahmood; Barzegar, Abdolrazagh; Khademi, Ali
Abstract Introduction We aimed to evaluate the relationship between suicide method, and gender, age, and level of education in a nationwide study in Iran over the period from 2006 to 2010. Methods Data on completed suicide cases referred to all forensic medicine centers throughout the country that were approved by an autopsy test were collected using data collection forms, which were filled out by the family members in interview sessions. Then, statistical analyses were performed using analysis of variance and chi‐square tests, as well as logistic regression analysis. Results Hanging is more popular among men (62.9% versus 27.7%), while self‐burning is preferable for women (39% versus 7%) (P < 0.0001). Younger individuals more frequently adopt a highly violent method, firearms (mean age of 27.1), while older persons more often use hanging and poisoning (mean ages of 32.4 and 32.1, respectively) (P < 0.0001). Hanging and self‐burning are more frequently used by persons with lower levels of education, whereas poisoning is more popular with more educated individuals (P < 0.0001). Discussion All of the studied variables, that is, gender, age, education level, are critical risk factors of adopting different suicide methods in an Iranian population. Future work is necessary to explore the psychopathology adopting different suicide methods in the Iranian population.